Juntos pelo acaso? Diferenças individuais e relacionamentos românticos - Oliveira, Jéssica Janine de (2020)
In the last decades, studies with sexual selection in the human species have turned their attention to individual aspects, such as: self-esteem, sociossexuality, personality, and attachment. Self-esteem is a social thermometer that indicates to an individual when he must change their behavior. Sociossexuality can be defined as a behavioral tendency of one person engage in casual sex. Personality is a set of psychological traits defined by the interaction between genetic predisposition and environment. The romantic attachment can be described as a set of behavioral tendencies that allow the individuals maintain emotional bonds. The aim of the present study was to investigate the relationship between self-esteem, sociossexuality, romantic attachment, personality, self-perceived mate value, idealization of a romantic partner and relationship satisfaction in heterosexual and non-heterosexuals individuals. 385 volunteers participated in this study, 219 singles and 166 in a long-term relationship (12 months or more of duration). The participation consisted in answer a package of questionnaires. Our results showed that heterosexual and non-heterosexual men and women differ in their idealization of a romantic partner, and self-esteem influence the idealization of a romantic partner. On the other hand, self-esteem does not differ between single and committed participants. The sociossexual orientation, the personality traits and the attachment dimensions are different between sex and sexual orientations. Also, the romantic attachment and personality traits could predict the self-perceived mate value and the partners evaluation of the individual’s mate value. The romantic attachment was the most capable of predicting relationship satisfaction when compare to the other studied variables. We suggest that the evolution of self-esteem, personality, sociossexuality and romantic attachment could have influenced the mate choice context.